ANALYSIS OF METHODS FOR CALCULATING BUILDINGS AND STRUCTURES UNDER DYNAMIC LOADS - Dilmuhammad Gulomov (Western European Studies, 2025)
The article will consider the analysis of methods of calculating buildings and structures to dynamic effects. Buildings and structures are affected not only by the load of certain elements of it, but also by the force of an earthquake (seismic). As a result, there have been cases of an earthquake affecting buildings and structures, causing it to crash status and decay. This has led to the study of the nature of building exposure through experiments and the emergence of several theories. Thanks to this, scientific work and research was carried out, allowing theories to be created
Keywords: Static; dynamic; spectral; theory